2021
DOI: 10.3390/ph14050399
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Antibacterial Screening of Some Novel Heteroaryl-Based Ciprofloxacin Derivatives as DNA Gyrase and Topoisomerase IV Inhibitors

Abstract: A novel series of ciprofloxacin hybrids comprising various heterocycle derivatives has been synthesized and structurally elucidated using 1H NMR, 13C NMR, and elementary analyses. Using ciprofloxacin as a reference, compounds 1–21 were screened in vitro against Gram-positive bacterial strains such as Staphylococcus aureus and Bacillus subtilis and Gram-negative strains such as Escherichia coli and Pseudomonas aeruginosa. As a result, many of the compounds examined had antibacterial activity equivalent to cipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The biosynthesized orange AgNPs peel extract demonstrated the best antioxidant activity in all experiments in this study, regardless of extraction solvent, as shown in Figure -4. The study showed that the inhibition zones of Ciprofloxacin and Voriconazole against bacteria and fungi were agree with Al-Wahaibi, et al, 2021 and Al-Nima, et al, 2020 results respectively (30,31). No inhibition zones were conducted with the examined plain citrus peel extracts against S. aureus, E coli and C. albicasns, this may be due to the extraction medium or the low concentration used in the research.…”
Section: Discussionsupporting
confidence: 78%
“…The biosynthesized orange AgNPs peel extract demonstrated the best antioxidant activity in all experiments in this study, regardless of extraction solvent, as shown in Figure -4. The study showed that the inhibition zones of Ciprofloxacin and Voriconazole against bacteria and fungi were agree with Al-Wahaibi, et al, 2021 and Al-Nima, et al, 2020 results respectively (30,31). No inhibition zones were conducted with the examined plain citrus peel extracts against S. aureus, E coli and C. albicasns, this may be due to the extraction medium or the low concentration used in the research.…”
Section: Discussionsupporting
confidence: 78%
“…Antibiotic resistance has generated a significant and inability to meet medical requirements for the research and establishment of innovative forms of antibacterial medications (Al‐Wahaibi et al, 2021; Bassetti et al, 2013; Frejat, Cao, Zhai, et al, 2022; Sugden et al, 2016; Toner et al, 2015; Ventola, 2015). The majority of present chemotherapeutics have acquired resistance in bacterial strains (Chan et al, 2015; Gardete & Tomasz, 2014; Müller et al, 2017), necessitating the hunt for novel antibiotics capable of suppressing resistance mechanisms.…”
Section: Biological Actionsmentioning
confidence: 99%
“…The evolution of drug-resistant strains, viz ., methicillin-resistant Staphylococcus aureus (MRSA) and Staphylococcus epidermidis (MRSE), has unfortunately augmented both nosocomial and inherent mortality rates, which poses an imperative threat to human health . Nowadays, the development of new antibacterial compounds to combat human bacterial infections has become a big challenge, and that may be related to the explicit and repeated use of antibiotics. , Recently, only four new classes of antibiotics have been approved by FDA over the past 17 years, while most current drugs have the same well-understood target. , The thiazole moiety is found in several substances, including thiamine (vitamin B1), thiamine pyrophosphate (TPP), bacitracin, amoxicillin, cefotaxime, and sulfathiazole. Additionally, thiazole derivatives have emerged as a new class of potent antimicrobial agents, which are reported to inhibit bacteria by many different mechanisms such as blocking the biosynthesis of certain bacterial lipids and inhibiting DNA gyrase B , and dihydrofolate reductase …”
Section: Introductionmentioning
confidence: 99%
“…5,6 The thiazole moiety is found in several substances, including thiamine (vitamin B1), thiamine pyrophosphate (TPP), bacitracin, amoxicillin, cefotaxime, and sulfathiazole. 7−10 Additionally, thiazole derivatives have emerged as a new class of potent antimicrobial agents, which are reported to inhibit bacteria by many different mechanisms such as blocking the biosynthesis of certain bacterial lipids 11 and inhibiting DNA gyrase B 12,13 and dihydrofolate reductase. 14 Pyrazole is one of the most prevalent nitrogen heterocyclic cores in many biologically active natural and synthetic compounds, which has received substantial attention in medicinal chemistry and drug design research.…”
Section: Introductionmentioning
confidence: 99%